Everything's Archie - Doyle, Frank 1917-1996; Hartley, Alex 1963-; Gladir, George 1925-2013 (Archie Comics, 2018)
"Back in the days of Saturday morning cartoons, The Archies ruled both TV and radio. While 'Sugar Sugar' was on the airwaves, you could also read the band's adventures in this classic series--reprinted here for fans young and old alike! This chronological collection features over 30 stories from the Everything's Archie comics series."--
Keywords: Archies; Jugend; Musik; Comic